UN 2023 Water Conference highlights the importance of systems thinking - McCartney, Matthew P.; Ringler, Claudia; Khadka, Manohara; Hafeez, Mohsin (CGIAR System Organization, 2023)
The global water crisis is worsening. This was confirmed at the recently concluded United Nations 2023 Water Conference. Despite the need for action being highlighted nearly 50 years ago at the last major UN water conference in Mar del Plata, Argentina, several billion people continue to lack secure access to water; water shortages, but also floods, increasingly contribute to food shortages and hunger; and energy security goals are in peril due to growing water variability and depletion.